The Relationship Between Business Strategy and Customer Satisfaction: A study of South African business performance - Yolanda Jordaan; Jacobus Johannes Badenhorst (Profesional Muda Cendekia Publishing, 2022)
The purpose of this paper is to investigate the inter-connected relationships of business strategy, customer satisfaction and business performance. Data was collected from senior executives in small, medium, large and corporate businesses in South Africa, and supplemented with existing available national customer satisfaction data. A total sample of 1,069 business leaders was realised of which 64 businesses had available customer satisfaction data. Findings revealed a relation between a clear business strategy and high levels of customer satisfaction. More importantly, both business strategy and customer satisfaction differentiate businesses on overall performance/success. This single survey study could not capture business-performance drivers within a value chain of decisions, actions and outcomes. The association between business strategy and customer satisfaction cannot be ignored by practitioners who aspire to improve business performance. Thus, if customer satisfaction aligns with a clear business strategy it can provide superior business performance in comparison to industry competitors. These results show conclusively that the clarity of a business’s purpose, through consistently prioritising one of Porter’s generic strategies, succeeds in satisfying customers. While previous research analysed the relationship between both business strategy and customer satisfaction with business performance, the originality of this study lies in linking business strategy with customer satisfaction. Furthermore, the research adapted existing business measurements to bring it in line with Porter’s generic strategies, and then adjusted the strategy classification to be consistent with how businesses prioritise strategies.